SEKSISME DALAM LAGU BOJOKU GALAK VIA VALEN - Ida Herawati (Balai Bahasa Kalimantan Barat, 2018)
Sexism is a form of gender discrimination that has occurred from antiquity. Sexism can be experienced by both men and women. Sexism occurs not only in action, but it can occur in the use of language as well. One form of discrimination that occurs in women is through the song. Many of the song lyrics that were created both in Indonesian and in particular Java is a whiny song, which exploits the suffering of life, especially women. The object of this research is the lyrics of Java Bojoku Galak by Via Valen. The song is accompanied in dangdut koplo. In the Javanese song depicts the attitude of a wife's nerimo in accepting destiny. The purpose of this study was to analyze the lyrics of songs containing sexism. The method used in this research is qualitative method.